Особливості забезпечення якості та тарифного регулювання послуг теплопостачання - Гунька, Б. В.; Дацюк, А. М.; Гавран, В. Я.; Hunka, B. V.; Datsiuk, A. M.; Havran, V. Y. (Видавництво Львівської політехніки, 2023)
У статті розглянуто стан надання теплопостачальних послуг. Систематизовано показники якості послуг централізованого теплопостачання. У результаті дослідження якості послуг теплопостачання виявлено, що така оцінка зводиться до мінімальних технічних вимог та умов взаємовідносин зі споживачами. Для підвищення якості теплопостачальних послуг запропоновано запровадити моніторинг на основі розрахунку інтегрального показника якості, який містить такі складові, як комерційна якість послуг теплопостачання, безперервність надання, доступність і технічна якість.

The article deals with studying the state of providing heat supply services. The quality indicators of centralized heat supply services have been categorized. The evaluation of the quality of centralized heat supply services hinges on principal benchmarks such as punctuality in starting and finishing the heating season, uninterrupted service provision, and adherence to current regulations. Having analysed the heat energy supply, its pricing was divided into two components – conditionally permanent and conditionally variable. Such division allows us to mitigate the adverse effects of the seasonality of this housing and communal services category. It‘s noteworthy that this tariff formation developed with the ‘cost plus‘ method (which also includes heat energy losses), is assumed imperfect according to European standards. It provides only a minimal level of profitability, which neither fosters equipment development nor encourages cost savings nor motivates employees. The study on the quality of heat supply services revealed that the assessment was primarily based on the minimum technical requirements and consumer relations. The article states that the principal challenge in providing high-quality heat supply services is the lack of competition in this sector. Heat supply enterprises do not have enough incentives to enhance their efficiency and seek opportunities for implementing investment programmes to ensure a more cost-effective service supply. To improve quality and resolve current issues the authors propose to adopt non-conventional measures, to investigate changes in the quality of heat supply services and how they are evaluated by consumers, to inform the regulatory housing and communal services authorities and local self-government bodies about the existing problems of heat supply services and their quality so that they can make effective management decisions. For the purpose of enhancing the quality of heat supply services, it has been recommended to use monitoring based on the integrated quality index calculation. This index comprises elements such as commercial service quality, service reliability, service accessibility, and technical quality.
Features of quality assurance and tariff regulation for heat supply services
Keywords: житлово-комунальне господарство; тарифне регулювання; житлово-комунальні послуги; якість послуг теплопостачання; housing and communal economy; tariff regulation; housing and communal services; heat supply service quality; 332.8[338.532.4; 338.465]